Effect of the intermediate pedicle screws and their insertion depth on sagittal balance and functional outcomes of lumbar fracture - Deng, Lei; Zhang, Junxin; Zhou, Quan; Zheng, Yifei; Hua, Xi; Hu, Xiayu; Liu, Hao; Qian, Zhonglai (Frontiers in Surgery, 2022)
Objective： To study the effect of the intermediate pedicle screws and their insertion depth on sagittal balance and functional outcomes of lumbar fracture. Methods： This study reviewed 1123 patients with lumbar fracture between January 2015 and June 2019, and 97 patients were ultimately enrolled in this study. Group A: 32 patients in the 4-pedicle screws fixation group, Group B: 28 patients in the 6-pedicle screws fixation with long intermediate pedicle screws group, Group C: 37 patients in the 6-pedicle screws fixation with short intermediate pedicle screws group. The radiographic outcomes were assessed with lumbar lordosis (LL), segmental lordosis (SL), fractured vertebral lordosis (FL), sacral slope (SS), pelvic incidence (PI), and pelvic tilt (PT). The visual analog scale (VAS) and the Oswestry disability index (ODI) scores were used for assessing functional outcomes. Results: The PI, PT and SS showed no significant differences between three groups (P>0.05). Compared with Group A, Group B and Group C showed better FL, SL and LL 1 months after operation(5.96±1.67/4.81±1.49 vs.8.78±2.90, 24.39±3.80/23.70±4.10 vs.20.09±3.33, 39.07±3.61 /39.51±3.23 vs.36.41±3.11, P<0.05) and at final follow-up (8.75±1.40/6.78±1.70 vs.11.31±2.61, 22.11±3.39/23.70±4.10 vs. 17.66±2.60, 38.04±3.49/39.51±3.23 vs. 35.41±3.11, P<0.05). The FL of Group C were significantly better than those of Group B 1 months after operation (4.81±1.49 vs.5.96±1.67, P<0.05) and at final follow-up (6.78±1.70 vs.8.75±1.40, P<0.05). No significant differences of VAS and ODI were found between Group A and Group B (P>0.05). There were also no significant differences of VAS and ODI between Group A and Group C (P>0.05). However, The VAS and ODI of Group C showed better than Group B 1 months after operation (3.05±0.70 vs.3.54±0.79, 17.65±3.41 vs.19.71±2.35, P<0.05) and at final follow-up (2.19±0.46 vs.2.57±0.57, 13.81±2.20 vs.15.57±1.73, P<0.05). Conclusions: Both 4-pedicle screws fixation and 6-pedicle screws fixation were effective in treating lumbar fracture. However, 6-pedicle screws fixation with short intermediate pedicle screws showed better radiographic and functional outcomes after surgery. Therefore, we recommend 6-pedicle screws fixation with short intermediate pedicle screws from the long-term recovery of sagittal balance and function.